(3GdfXGe GdbGfhfj ddNUheI CeGe eMceI GdEMGdI HYO GdfbV (B/s - (3GdfjOGfj, GdCfUGQj MSfs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2002)
(3eGPG HYO GdfbV,MGdGJ GdfbV Ohf EMGdI,MGdGJ GdfbV hGdbha Yf gPG GdMO,fbV GdMce hGdaUd ajg,GdMGdGJ GdJj jLH ajgG EMGdI GdOYhi,GdeMceI GdJj JMGd EdjgG GdbVjI,GdJYLjd aj GdbGfhf GdeUQj,eQGMd GdNUheI hYhGQVgG,fWGb GdNUheI ef MjK GdWdHGJ,fWGb GdNUheI ef MjK GdOahY Mce eMceI GdEMGdI hGdWYf ajg,SdWGJ eMceI GdEMGdI,ELQGAGJ WQM GdWYf hfXQg CeGe GdLeYjI GdecJedIs
(3HHdjhZQGajG(B:(3U(B.319-326s
Keywords: (3fbV GdCMcGes